Analysis Characteristics of On/Off Grid Tie Inverter and Implementation in Microgrid - Rudy Setiabudy; Hartono BS Hartono BS; Budiyanto Budiyanto (Universitas Ahmad Dahlan, 2013)
One characteristic of microgrid is possible to be integrated with the public electricity network (PLN/grid) or work independently of the public network. Additionally on microgrid is also possible to supply excess power to the grid and still be able to supply power to local load even when disconnected from grid. Not all inverter devices can be used on a microgrid, associated with some of the criteria that must be met. How do the characteristics of on-off grid tie inverter (GTI on-off) and how to build microgrid using on-off GTI became topic of this research activity. Based on results of testing, on-off GTI can be used on microgrid, with ability to supply power to network when excess power or supplied from network at the time of power shortage. As well as on-off GTI is able to work independently when there is no power from network.